Turismo Comunitario, Alternativa De Desarrollo Turístico Estudio De Caso: Turismo Rural Comunitario Para La Parroquia Cacha, Cantón Riobamba, Provincia De Chimborazo – Ecuador - Baquero, Juan Carlos Carrasco; Janeta, Laura Beatriz Sucuy; Velásquez, Carlos Renato Chávez (European Scientific Journal, ESJ, 2016)
Ecuador is recognized as a country with the richest biodiversity on the planet, especially in relation to its size. For its variety of natural and cultural settings, it is even considered a magical place. Tourism is currently an activity that is generating considerable foreign income and employment for Ecuador, as well as maintaining and restoring cultural traditions and natural areas in sustainable ways. Rural, community-based tourism is one form that attempts to integrate community members with tourists in an intercultural setting, while ensuring sufficient management of the experience that natural resources, heritage values and cultural rights are preserved. In Chimborazo, a larger percentage of the indigenous population than in any other province is engaged in community-based tourism, creating experiences that complement tourist visits to natural attractions. Within this context is the rural parish of Cacha, with its unique natural landscapes and rich history, considered the origin of the Great Puruwá Nation. Following a market study on generating community-based tourism in Cacha, we conclude that the concept has wide local acceptance and that there is a high demand among tourists who would be interested in learning about this region and enjoying its benefits. Additionally, marketing tourist products assists communities in maintaining their traditions and motivates young people to generate new economic activity.